Análise do secretoma do fungo Trichoderma harzianum crescido em presença de glicose ou parede celular de Fusarium solani - RAMADA, Marcelo Henrique Soller (2010)
Trichoderma harzianum is a saprophytic fungus, known for its potential as a biological control agent of different phytopathogens that causes losses in crops. Its action is based on different mechanisms like volatile and non-volatile antibiotics production, competition for nutrient and space, production of hydrolytic enzymes and mycoparasitism. Fusarium solani is the agent of bean dry root rot, and is responsible for significant losses. This work sought to analyze and identify secreted proteins from T. harzianum grown in the presence of F. solani cell wall, in an attempt to obtain new insights on biocontrol.In the dual culture test, T. harzianum proved to be a potent antagonist of F. solani. Some differences in the secreted proteins profile and final medium pH were observed when T. harzianum was grown in TLE medium containing glucose and in TLE and Minimum medium containing the cell wall of the phytopathogen. 33 proteins from 18 different genes were identified. The protein Sm1 was identified and secreted in all growth conditions. Many hydrolytic enzymes related to mycoparasitism, like endochitinases, β-1,3, β-1,6-glucanases, proteases and α-1,3-glicanases, were identified and among the proteases, a hypothetical metalocarboxipeptidase and a serine subtilisin-like never described for T. harzianum. Some enzymes with unkown roles in the mycoparasitism, such as β-1,3-glucanosyltransferase, secreted only in MM growth medium supernatant, were also identified.